The graded distribution of the dorsal morphogen is initiated by selective nuclear transport in Drosophila. - Rushlow, C.A.; Han, K.; Manley, J.L.; Levine, M. (Cell, 1989)
The maternal morphogen dorsal (dl) plays a key role in the establishment of dorsal-ventral polarity in Drosophila. We present evidence that the graded distribution of dl protein is initiated by selective nuclear transport. The dl protein is uniformly distributed throughout the cytoplasm of early embryos, but approximately 90 min after fertilization, dl protein present in ventral but not dorsal regions is selectively transported to the nucleus. Mutations in maternally active genes that regulate dl disrupt this transport process, resulting in an inactive, cytoplasmically localized form of the dl protein. Selective nuclear transport of dl protein was reproduced in tissue culture cells. The wild-type dl protein is largely restricted to the cytoplasm, while truncated proteins are predominantly localized within the nucleus. Transient cotransfection assays suggest that dl activates expression from several promoters in an apparently sequence-independent manner. We discuss the role of nuclear transport as a regulated process in gene expression and development.